The Psychological Responses of Elite Equestrian Athletes to Their Horses' Injuries - Emma Davies; Victoria Loyer (International Journal of Equine Science, 2023)
Equestrian sport requires optimal performance from horse and rider for a successful partnership, and the high-risk nature increases the injury risk for both parties. Negative psychological responses have been reported following equine injury in amateur and youth riders, but little is known about elite athletes, for whom the horse-rider relationship may be more transactional than familial. The aim was to investigate the psychological responses of elite riders to their horses' injuries. Twelve international riders (8 women, 4 men, x̄ = 30.8 ± 10.8 years (range 20–51 years), who had competed from CCI-2* to the Olympics and World Equestrian Games (WEG), were interviewed about their experiences of equine injury. Interview questions explored athletes' careers, initial reactions, coping mechanisms, and return to elite competition. Thematic analysis revealed three themes: cognitive appraisal, emotional responses, and coping strategies. Riders reported a sense of loss, and several felt this impacted their athletic identity. All riders reported a sense of duty towards their horse. Elite athletes experienced negative emotional responses, including devastation, frustration, denial, and guilt, at the onset of equine injury. Several coping strategies were utilized, including avoidance and reliance on social support, and some riders also reported personal growth. Elite riders reported wider psychological impacts on support networks and responses were shaped by the normalization of injury within the equestrian community. Further research should explore the benefits of intervention programs on equestrian athletes' coping strategies, as well as the impact of equine injury on the mental health of grooms.